Statistical evidence in medical trials : what do the data really tell us? - Simon, Stephen D. (Oxford statistics., 2006)
Statistical Evidence in Medical Trials is a lucid, well-written and entertaining text that addresses common pitfalls in evaluating medical research. Including extensive use of publications from the medical literature and a non-technical account of how to appraise the quality of evidence presented in these publications, this book is ideal for health care professionals, students in medical or nursing schools, researchers and students in statistics, and anyone needingto assess the evidence published in medical journals.